2017
DOI: 10.14202/vetworld.2017.769-773
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping, antibiotic susceptibility, and virulence genes screening of Escherichia coli isolates obtained from diarrheic buffalo calves in Egyptian farms

Abstract: Aim:In Egypt as in many other countries, river water buffalo (Bubalus bubalis) is considered an important source of high-quality milk and meat supply. The objective of this study was to investigate serotypes, virulence genes, and antibiotic resistance determinants profiles of Escherichia coli isolated from buffalo at some places in Egypt; noticibly, this issue was not discussed in the country yet.Materials and Methods:A number of 58 rectal samples were collected from diarrheic buffalo calves in different regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 118 publications
4
8
0
3
Order By: Relevance
“…In the current study, the E. coli serotyping revealed the serogroups; O86, O119, and O158, which were also demonstrated in diarrheic calves from Egypt by a previous report (Hakim et al 2017). The serogroups; O18, O143, O1and O63 are specified in our survey and had a different variety than previous studies (Hakim et al 2017;Vu-Khac and Cornick 2008), and to the best of our knowledge, this is the first report of these serogroups (O18, O143, O1, and O63) in E. coli strains identified from pneumonic calves in Egypt. Further, most E. coli strains isolated from healthy and pneumonic calves carry one to three virulence genes; fimH, eaeA and hly.…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, the E. coli serotyping revealed the serogroups; O86, O119, and O158, which were also demonstrated in diarrheic calves from Egypt by a previous report (Hakim et al 2017). The serogroups; O18, O143, O1and O63 are specified in our survey and had a different variety than previous studies (Hakim et al 2017;Vu-Khac and Cornick 2008), and to the best of our knowledge, this is the first report of these serogroups (O18, O143, O1, and O63) in E. coli strains identified from pneumonic calves in Egypt. Further, most E. coli strains isolated from healthy and pneumonic calves carry one to three virulence genes; fimH, eaeA and hly.…”
Section: Discussionsupporting
confidence: 85%
“…A previous study from Egypt in diarrheic buffalo-calves farms reported that the most prevalent phenotypic resistance patterns were; ampicillin (71.4%) and amoxicillin (64.3%), as well as trimethoprim/sulfamethoxazole (50%) and gentamicin (42.8%) [ 26 ]. A previous study in Iran reported that E. coli strains retrieved from diarrheic calves showed maximum resistance to penicillin, streptomycin, tetracycline, lincomycin and sulfamethoxazole [ 27 ]. The resistance pattern observed in our study and the previous other studies indicated that the emergence of multidrug-resistant species has become an increasing problem worldwide, due to the overuse of antimicrobial drugs in both animal and human medicine [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to El-Shazly et al (2017), many farmers in Egypt tend to use cefotaxime injections (a 3rd generation cephalosporin banned in poultry) to treat diseases in chicken (such as colibacillosis) after the failure of other antimicrobial treatments like fluoroquinolone and aminoglycosides. In addition, due to the low cost of antibiotics, many veterinarians still over-use antibiotics such as tetracycline, quinolone and beta lactams to treat and prevent zoonotic diseases and growth promotion (Braun et al, 2016; Hakim et al, 2017). Moreover, in pets, blaTEM along with blaSHV, blaPSE-1 and blaCTX-M were detected in E. coli strains isolated from dogs in in the same country (Aly et al, 2012).…”
Section: Distribution Of Multi-drug Resistant Organisms In Animalsmentioning
confidence: 99%